Effects of combined aerobic and resistance training compared to aerobic training alone on physical fitness and cognitive function in overweight and obese older adults: a randomized controlled trial - Zhao, Changyuan; Omar Dev, Roxana Dev (Asociacion Espanola de Analisis del Rendimiento Deportivo, 2025)
The problem of obesity among older adults is becoming increasingly serious, leading to declines in physical fitness and cognitive function. While aerobic exercise (AE) is widely recommended for improving cardiometabolic health, combining it with resistance training (CARE) may yield broader functional benefits. This study aimed to evaluate and contrast the impacts of AE and CARE interventions on physical fitness and cognitive performance among older adults with overweight or obesity. A 12-week randomised controlled trial was conducted involving 46 overweight and obese older adults. Participants were randomized to aerobic exercise (AE) or AE + resistance training (CARE). Outcomes included body composition, senior fitness, and neuropsychological assessments. Both improved, with distinct effects: AE yielded greater reductions in weight, BMI, fat mass, and waist-hip ratio; CARE increased skeletal muscle mass, had larger strength gains, and showed greater improvements in Mini-Mental State Examination and memory tasks. Both benefit physical and cognitive outcomes in obese older adults. AE is particularly effective for fat reduction, while CARE confers additional advantages in muscle preservation, strength, and cognition. CARE may therefore represent a more comprehensive intervention to enhance health aging and maintain daily independence in this population.